Layang Teacher Platform in the Cyber Pedagogy Room - Prayetno Prayetno; Muhammad iqbal; Jamaludin Jamaludin; Windawati Pinem (Green Publisher Indonesia, 2022)
This article research aims to examine the readiness of learning in the digital arena for teachers and students through the application of the “Teacher Layang” platform. How are student learning activities and teacher establishment in carrying out the teaching and learning process in the cyber pedagogy space. Through the fly teacher platform, student learning outcomes are expected to be able to organize learning outcomes optimally because there are no supporting e-learning media facilities and the readiness of teachers who seem digitally stuttered so that learning orientation takes place less effectively. The floating teacher platform based on android and web becomes a simple e-learning media with the principles of learning theory and learning outcomes. This research uses a qualitative approach with a case study method. The object of research is teachers and students. Data were obtained through observation, interviews, FGD (focus group discussions) and documentation studies. The data analyzed consisted of three activity lines, namely data reduction, data presentation and conclusion drawing. The findings of this study through the floating teacher platform have shown changes in achievement, teachers can easily manage digital classes to the maximum, from communication with students, presenting material to assessment. Teacher creativity can be implemented through the platform in the cyber pedagogy space. Students who seem to have facilitated their study room well and are fun. Teachers in maturity in the cyber pedagogy space are the main requirements to be able to organize distance learning activities, so that students will respond with the management of the learning process that has been prepared by the teacher. The fly teacher platform is an adequate attribute of cyber pedagogy for teaching and learning activities effectively and optimally.